Schoengastia propria Audy and Womersley 1957 - Stekolnikov, Alexandr A. (Zenodo, 2021)
Schoengastia propria Audy and Womersley, 1957 Schoengastia propria Audy and Womersley, 1957: 367, fig. 8; Nadchatram et al. 1980: 269, 280; Fernandes & Kulkarni 2003: 324, fig. 106; Chaisiri et al. 2016: 332. Schoengastia (Schoengastia) propria : Vercammen-Grandjean 1965b: 82. Type deposition. ZSI. Type data. Ex Fowlea piscator (syn. Natrix piscator ), India, Bombay (currently Mumbai). Hosts. RODENTIA: Bandicota indica, Rattus rattus SQUAMATA: Fowlea piscator . Distribution. India, Thailand. Published as part of Stekolnikov, Alexandr A., 2021, A checklist of chigger mites (Acariformes: Trombiculidae) of Southeast Asia, pp. 1-163 in Zootaxa 4913 (1) on page 94, DOI:10.11646/zootaxa.4913.1.1, http://zenodo.org/record/4448915